The effect of low-intensity pulsed ultrasound therapy on fracture healing - Jagannath B Kamath; Nikil Jayasheelan; Babul Reddy; Shafeekh Muhammed; Amaranth Savur (Wolters Kluwer Medknow Publications, 2015)
Purpose: Multiple methods of accelerating fracture healing have been proposed and some are approved for use in the clinical settings. A low intensity (30 nW/cm 2 ) pulsed ultrasound (LIPUS) signal will promote fracture healing. This study is conducted to determine the effect of LIPUS on fresh fracture healing. Materials and Methods: Out of the 60 patients with diaphyseal fractures of the tibia and femur fixed with an interlocking nail, 33 received LIPUS and 27 were kept as control. Ultrasound treatment was started three days after surgery, 20 minute sessions each day, for 30 days. The rate of fracture healing in the LIPUS group was compared with that of the control group. Six orthopedic surgeons and two radiologists analyzed the follow-up x-rays. Results: Five out of the six surgeons interpreted that there was significantly more callus formation and union in the LIPUS group compared to the control group, especially in the initial stage of healing. The need for dynamization decreased by 50% in the LIPUS group. Both radiologists interpreted that there was significantly more callus in the case where ultrasound was administered, when they evaluated the same with an diagnostic ultrasound scan at the fracture site. Conclusion: The present study establishes the relation between low intensity pulsed ultrasound therapy and fresh fracture healing, especially in the early stages. We strongly recommend the use of LIPUS as an adjunct therapy where the surgeon anticipates delayed union of the fracture.